Efficacy of Contoya plant (Lobelia decurrens Cav.) to control coccidiosis in calves - Torrel, Teófilo; Valle, Julissa; Pérez, Fredesbinda; Rojas-Moncada, Juan; Vargas-Rocha, Luis (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Cattle are susceptible to infections by parasitic protozoa, which often require chemical treatments. However, using these products can contaminate the soil and negatively affect ecosystems (flora, fauna and microbiota), affecting the food chain and safety by leaving residues in milk and meat and posing risks to consumers. Therefore, it is crucial to seek sustainable alternatives, such as using bioactive plants and their extracts. Objective: To evaluate the efficacy of contoya plant (Lobelia decurrens Cav.) at single doses of 1 g.kg-1 and 2 g.kg-1 of body weight for controlling coccidiosis in naturally infected calves under extensive rearing conditions. Methods: Groups of calves with similar parasitic loads (ANOVA p>0.05) were formed and orally administered pulverized leaves and flowers of contoya plant. Efficacy was calculated as the percentage reduction of oocysts per gram of feces using a McMaster chamber. Results: The 2 g.kg-1 dose significantly reduced the parasitic load compared to the 1 g.kg-1 dose (p<0.05). With a dose of 1 g.kg-1, a minimum efficacy of 38.04% was observed on the third day and a maximum efficacy of 86.93% on the fifteenth day. With the 2 g.kg-1 dose, a minimum efficacy of 73.91% was achieved on the third day and a maximum efficacy of 95.45% on the fifteenth day. Conclusion: Our results indicate that contoya at a dose of 2 g.kg-1 body weight can control coccidiosis in calves. This could be advantageous for cattle producers, providing a superior alternative to conventional drugs in terms of costs, environmental impact, as well as food safety and quality.